RISK MITIGATION OF NEGATIVE PLEDGE COLLATERAL FOR SYNDICATED LOAN IN OIL AND GAS COMPANY - Prabeswara, Yudho (Awang Long Law Review, 2025)
Lending by banks carries the risk of default, which may affect the bank’s financial stability. To reduce this risk, banks apply prudential principles in syndicated loans, including the Negative Pledge mechanism, which prohibits debtors from encumbering their assets to other parties without creditor approval. However, as a state-owned company, PT P has limitations in using its assets as collateral, so using a Negative Pledge is an alternative solution. The challenge is that this clause has no specific regulation in Indonesia, which can weaken the creditor’s position in the credit agreement. This research aims to analyze the application of Negative Pledges in syndicated loans in the oil and gas sector and identify risk mitigation strategies for creditors in Indonesian law. The research method used is descriptive with a normative approach based on analysis of positive law, jurisprudence, and legal doctrine. The findings reveal that although the Negative Pledge clause provides significant protection to creditors, its implementation in Indonesia faces challenges due to the absence of specific regulations governing the clause in detail. Additional clauses such as Disposal Restrictions are recommended to mitigate risks, along with enhanced oversight through more stringent agreement mechanisms. This study offers practical contributions to banks in managing syndicated loan risks and provides new insights into the development of banking legal policies related to the Negative Pledge in Indonesia.